1,3,3-Trimethyl-1,2,3,4-tetrahydropyrido[1,2-a]benzimidazol-1-ol - Sayed Hasan Mehdi; Rokiah Hashim; Raza Murad Ghalib; Chin Sing Yeap; Hoong-Kun Fun (Acta Crystallographica Section E, 2010)
In the title compound, C14H18N2O, the benzimidazole grouping is close to planar, with a maximum deviation of 0.042 Å; the six-membered non-aromatic ring adopts an envelope conformation. In the crystal structure, molecules are linked into infinite sheets lying parallel to the bc plane by O—H...N and C—H...O hydrogen bonds.